Postoperative pain after root canal filling with different endodontic sealers: a randomized clinical trial - Nadia de Souza FERREIRA; Elisa Korte Fortes GOLLO; Noeli BOSCATO; Ana ARIAS; Emmanuel João Nogueira Leal da SILVA (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract The aim of this randomized clinical trial was to compare the occurrence and intensity of postoperative pain and analgesic intake after root canal treatment, using different root canal sealers. Sixty single-rooted teeth diagnosed with asymptomatic necrosis and apical periodontitis were randomly assigned to 3 experimental groups (n=20), according to the root canal sealer: AH Plus, Endofill or MTA Fillapex. Endodontic treatment was performed in two sessions, and calcium hydroxide was used as the intracanal dressing. Patients were instructed to record pain intensity as none, slight, moderate and severe. Scores from 1 to 4 were attributed to each level of pain after 24 h, 48 h and 7 days. The need for analgesic intake was also recorded. Differences in the incidence of postoperative pain and the need for an analgesic were analyzed using the chi-square test. Differences in pain intensity after treatment were analyzed using the ordinal (linear) chi-square test. No significant differences were detected among the groups in terms of either incidence or intensity of postoperative pain, or need for analgesic intake, at any timepoint (p>0.05). No pain was reported after 7 days. AH Plus, Endofill and MTA Fillapex used for filling root canals resulted in the same rate of postoperative pain and need for analgesic medication.